Investigation of the impact of building orientation on cooling loads in an office building in the tropical climate - Maqbul Kamaruddin (Journal of Science, Technology, and Visual Culture, 2021)
The building sector ranks second behind the fossil fuel burning industry. This figure may significantly rise when the total number of buildings and cooling demands increases, as well as poor HVAC system usage. In tropical climates such as Indonesia, building energy consumption is dominated by cooling loads on air conditioners to reduce indoor temperatures. This study focuses on the orientation of buildings in tropical climates on the amount of cooling load in a mid-rise rental office tower: WTC 5 in Jakarta. Several Energy Plus simulations utilising real building characteristics were performed to assess the impact and capacity of cooling loads on various building levels. The current 45°N building is turned clockwise, and cooling demands are computed and compared. The evidence found from simulations in five building scenarios shows several data on each building floor. The south-oriented building can maximise the lowest cooling load of 7.47 kWh, which is quite far from the existing building and the east-west orientation is 7.72 kWh and 7.80 kWh at the same time. The resulting curve can be interpreted that the orientation of the building has an enormous impact in terms of the effect of cooling loads on buildings, especially in tropical climates.